Financial accounting applications 1 - Pascoe, Ian.; Carr, Peter (Peter W.) (Melbourne : Nelson, 1994)
This book is divided into four parts: basic management reports and analysis; Single-entry systems; One-write systems; and Non-for-profit organisations.
Keywords: Accounting; Economics; Accounting; Accounting -- Problems, exercises, etc